PENGARUH PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TEKNIK DUA TINGGAL DUA TAMU TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII SMPN 14 PADANG TAHUN PELAJARAN 2013/2014 - Rahmawati, Indri; Rahmi, Rahmi; Lovia, Lita (STKIP PGRI Sumbar, 2013)
The research was motivated by the studentsâ comprehension of math concept are still low at SMPN 14 Padang. This research aims to determine the studentsâ comprehension of math concept that apply Two Stay Two Stray better than studentsâ comprehension of math concept that apply conventional learning in class VIII SMPN 14 Padang. The type of research is experimental by using Randomized Control Group Only Design. The data analysis technique used is T-Test one part the help of MINITAB. The result of hypothesis test obtained P-Value = 0,011 is less than Î± = 0,05, then the hypothesis in this research received. In conclusion, studentsâ comprehension of math concept that apply Two Stay Two Stray type better than studentsâ comprehension of math concept that apply conventional learning.